Recurrent mutations of NOTCH genes in follicular lymphoma identify a distinctive subset of tumours. Issue 3 (18th September 2014) - Karube, Kennosuke; Martínez, Daniel; Royo, Cristina; Navarro, Alba; Pinyol, Magda; Cazorla, Maite; Castillo, Paola; Valera, Alexandra; Carrió, Anna; Costa, Dolors; Colomer, Dolors; Rosenwald, Andreas; et al.
Abstract Follicular lymphoma (FL) is one of the most common malignant lymphomas. The t(14;18)(q32;q21) translocation is found in about 80% of cases and plays an important role in lymphomagenesis. However, the molecular mechanisms involved in the development and transformation of this lymphoma are not fully understood. Gain‐of‐function mutations of NOTCH1 or NOTCH2 have recently been reported in several B cell lymphoid neoplasms but the role of these mutations in FL is not known. In this study we investigated the mutational status of these genes in 112 FLs. NOTCH1 and NOTCH2 mutations were identified in five and two cases, respectively (total 7/112, 6.3%). All mutations predicted for truncated protein in the PEST domain and were identical to those identified in other B cell lymphoid neoplasms. NOTCH‐mutated FL cases were characterized by lower frequency of t(14;18) (14% versus 69%, p = 0.01), higher incidence of splenic involvement (71% versus 25%, p = 0.02) and female predominance (100% versus 55%, p = 0.04). A diffuse large B cell lymphoma (DLBCL) component was more frequently identified in NOTCH‐mutated FL than in wild‐type cases (57% versus 18%, p = 0.03). These results indicate that NOTCH mutations are uncommon in FL but may occur in a subset of cases with distinctive, characteristic, clinicopathological features. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.